The Effectiveness of Orange Essential Oil Aromatherapy on Blood Pressure, Pulse Rate, and Respiratory Rate of Patients Scheduled for Coronary Angiography: A Clinical Trial - Homyra Tahmasebi; Elieh Abasi; Sakineh Pourhosein (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Patients scheduled for angiography experience pre-operative anxiety, which affects vital signs. Objectives: The current study aimed to investigate the effectiveness of orange essential oil aromatherapy on blood pressure, pulse rate, and respiratory rate of patients before coronary angiography. Methods: In this clinical trial, 70 patients scheduled for coronary angiography were separated into two groups of intervention and control. For those in the intervention group, two drops of orange essential oil were drip by emitters on a polyethylene handkerchief attached to the collar of the participants. Then, they were asked to breathe normally for 20 minutes. Vital signs were recorded before and after providing the intervention. Data were analyzed using SPSS version 16 using Chi-square, Fisherchr('39')s exact test, independent t-test, U Mann-Whitney, Paired Wilcoxon, and paired t-test. Results: There was no significant difference between the two groups concerning the mean vital signs before providing the intervention. However, after providing the intervention, a significant difference was found concerning pulse rate (71.3±26.79), respiratory rate (15.2±11.04), and systolic blood pressure (117.9±31.47) between the two groups (P<0.001). In the control group, no significant difference was found concerning the pulse rate (75.3±06.72), respiratory rate (17.2±18.28), and systolic blood pressure (123.8±91.91) before and after providing the intervention (P>0.001), and this difference was significant between the two groups (P<0.001). Also, there was no significant difference between the two groups concerning the diastolic blood pressure (P>0.001). Conclusion: This study demonstrated that orange essential oil, as a complementary method, can reduce pulse rate, respiratory rate, and systolic blood pressure in people undergoing coronary angiography. Therefore, it can be considered as a safe and cheap alternative therapeutic option